1987
DOI: 10.1002/bjs.1800740308
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatic rupture of the diaphragm

Abstract: Traumatic rupture of the diaphragm is a potentially serious injury which presents in different forms depending on the mechanism of the causative trauma. Over a 7 year period, 20 patients (17 male and 3 female) with traumatic rupture of the diaphragm were seen in our unit; their mean age was 25.6 years. Automobile accidents caused the diaphragmatic injuries in 65 per cent of cases while falls from trees were the cause of injury in 10 per cent. Ten patients (50 per cent) were seen within 7 days of the injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Blunt chest trauma has been studied extensively in other parts of Nigeria. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 ] The various studies in different parts of Nigeria have revealed the same socioeconomic characteristics of patients sustaining blunt chest trauma with rib fractures with predominance of male, young age group, and road traffic accident as the predominant cause. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 ] A particular study on blunt chest trauma in Enugu, Nigeria, specified that ICNB was the best pain control measure in patients sustaining rib fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt chest trauma has been studied extensively in other parts of Nigeria. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 ] The various studies in different parts of Nigeria have revealed the same socioeconomic characteristics of patients sustaining blunt chest trauma with rib fractures with predominance of male, young age group, and road traffic accident as the predominant cause. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 ] A particular study on blunt chest trauma in Enugu, Nigeria, specified that ICNB was the best pain control measure in patients sustaining rib fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Nas HDT, o diafragma esquerdo é acometido em cerda de 90% dos casos, tendo baixa incidência à direita, pois o fígado dissipa a energia do impacto 3 . O acometimento bilateral ocorre em aproximadamente 1% dos casos 1 .…”
Section: Discussionunclassified
“…Apesar da recomendação do acesso torácico, nos casos de HDT crônica 2 , a via de acesso abdominal montrou-se adequada para a correção de ambas as lesões gástrica e diafragmática. Atualmente, o acesso videolaparoscópico tem sido cada vez mais utilizado, permitindo o diagnóstico pela visualização da lesão diafragmática com maior especificidade em relação a outros métodos diagnósticos 3 . Possibilita, ainda, a redução dos órgãos herniados e a correção do defeito diafragmático por meio de sutura primária, utilizando como artifício a diminuição dos níveis de pressão do pneumoperitônio, o que permite a realização da sutura sob menor tensão 5 .…”
Section: Discussionunclassified
“…Diagnosis can be confirmed by radiological screening of the diaphragm, passage of a nasogastric tube, a barium meal or enema and by real‐time sonography. Correct preoperative diagnosis has been achieved in 70‐85% of cases by these techniques 4 . We had time to carry out these investigations in only one patient, because the other 20 had severe associated injuries: 12 patients with penetrating abdominal and thoracic injuries were operated on without any further investigation.…”
Section: Discussionmentioning
confidence: 99%